Cockroaches: From Belief Narratives to the Contemporary Commercial Practice, or How Cockroaches Have Survived on Earth for More Than 320 Million Years - Marjanić , Suzana (Poznańskie Studia Slawistyczne, 2021)
The first segment of the zooethical article about cockroaches, insects of the order Blattodea, who have lived on Earth for more than 300 million years (cf. Grush, 2016) and will survive the apocalypse of climate change, is based on research by Russian folklorist Aleksandr V. Gura (Гура, 2005), who gives examples of beliefs about cockroaches from the Russian ethnotradition, which I then compare with examples from the Croatian ethnotradition.In the second part of the article, I problematize the contemporary attitude towards cockroaches, starting from the literary reality of the novel Kiklop (Cyclops, 1965) by Ranko Marinković – from “Maar-commercial” (“Maar-tonfilmska reklama”), Melkior’s critique of the ad-centric worldview that begins with his exit from the public toilet in the central town square. The ways in which insecticides are used against cockroaches (and other insects considered by modern civilization as pests) demonstrates that in the past at least some cultures – as Russian ethnotradition demonstrates – were far more considerate of cockroaches, as we suggested in the first part of this dichotomously structured article.